Detection of Schistosoma mansoni and Schistosoma haematobium by Real-Time PCR with High Resolution Melting Analysis - Hany, Sady; Hesham M., Al-Mekhlafi; Romano, Ngui; Wahib M., Atroosh; Ahmed K., Al-Delaimy; Nabil A., Nasr; Salwani, Dawaki; Awatif M., Abdulsalam; Init, Ithoi; Yvonne Ai, Lian Lim; Kek, Heng Chua; Johari, Surin (MDPI, 2015)
The present study describes a real-time PCR approach with high resolution melting-curve (HRM) assay developed for the detection and differentiation of Schistosoma mansoni and S. haematobium in fecal and urine samples collected from rural Yemen. The samples were screened by microscopy and PCR for the Schistosoma species infection. A pair of degenerate primers were designed targeting partial regions in the cytochrome oxidase subunit I (cox1) gene of S. mansoni and S. haematobium using real-time PCR-HRM assay. The overall prevalence of schistosomiasis was 31.8%; 23.8% of the participants were infected with S. haematobium and 9.3% were infected with S. mansoni. With regards to the intensity of infections, 22.1% and 77.9% of S. haematobium infections were of heavy and light intensities, respectively. Likewise, 8.1%, 40.5% and 51.4% of S. mansoni infections were of heavy, moderate and light intensities, respectively. The melting points were distinctive for S. mansoni and S. haematobium, categorized by peaks of 76.49 ± 0.25 °C and 75.43 ± 0.26 °C, respectively. HRM analysis showed high detection capability through the amplification of Schistosoma DNA with as low as 0.0001 ng/µL. Significant negative correlations were reported between the real-time PCR-HRM cycle threshold (Ct) values and microscopic egg counts for both S. mansoni in stool and S. haematobium in urine (p < 0.01). In conclusion, this closed-tube HRM protocol provides a potentially powerful screening molecular tool for the detection of S. mansoni and S. haematobium. It is a simple, rapid, accurate, and cost-effective method. Hence, this method is a good alternative approach to probe-based PCR assays.